Strategic management of technological learning : learning to learn and learning to learn-how-to-learn as drivers of strategic choice and firm performance in global, technology-driven markets /: learning to learn and learning to learn-how-to-learn as drivers of strategic choice and firm performance in global, technology-driven markets. (©2001) - Unknown
No abstract available